2009
DOI: 10.1093/bioinformatics/btp160
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Trace Annotation Server: automated enzyme function prediction in protein structures using 3D templates

Abstract: Summary:The Evolutionary Trace Annotation (ETA) Server predicts enzymatic activity. ETA starts with a structure of unknown function, such as those from structural genomics, and with no prior knowledge of its mechanism uses the phylogenetic Evolutionary Trace (ET) method to extract key functional residues and propose a functionassociated 3D motif, called a 3D template. ETA then searches previously annotated structures for geometric template matches that suggest molecular and thus functional mimicry. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…To guide the identification of CR, several computational approaches have been developed based on different principles. To cite some examples: catalytic site features, amino acid physicochemical character [1] , conserved functional groups density [2] , sequence analysis (conservation, patterns, conserved blocks along the sequence, evolution, entropy, among others) [3] , [4] , [5] , [6] , [7] , [8] , sequence and structure properties [9] , [10] , [11] , evolution and 3D structure information [12] , [13] , [14] , [15] , neural networks [16] , 3D structure combined with ionization properties of a residue and its vicinity in the structure [17] and combinations of several of the above mentioned [18] . Conservation is the natural and intuitive way to predict functional residues in proteins.…”
Section: Introductionmentioning
confidence: 99%
“…To guide the identification of CR, several computational approaches have been developed based on different principles. To cite some examples: catalytic site features, amino acid physicochemical character [1] , conserved functional groups density [2] , sequence analysis (conservation, patterns, conserved blocks along the sequence, evolution, entropy, among others) [3] , [4] , [5] , [6] , [7] , [8] , sequence and structure properties [9] , [10] , [11] , evolution and 3D structure information [12] , [13] , [14] , [15] , neural networks [16] , 3D structure combined with ionization properties of a residue and its vicinity in the structure [17] and combinations of several of the above mentioned [18] . Conservation is the natural and intuitive way to predict functional residues in proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, various computational filters select among those hits the ones that are least likely to arise by chance. In practice the Evolutionary Trace Annotation (ETA) server [54], depicted in Figure 2A, uses the ranked lists of evolutionarily important residues produced by Evolutionary Trace (ET) [55,56]. Top-ranked ET residues are good candidates for 3D templates because they are known to generally overlap functional sites and identify their determinants [57], such that their targeted mutations efficiently engineer proteins with selective separation of function or rewired functional specificity [58].…”
Section: Evolutionary Trace Annotationmentioning
confidence: 99%
“…2B). By comparison to the ETA method [54], this global analysis raised accuracy by 6% at 65% coverage (from 90% to 96% accuracy) at the substrate-specific fourth EC level. It also increased accuracy and coverage over standard BLAST annotation by 10% (from 85% to 95% accuracy also at 65% coverage, see Fig.…”
Section: Networkmentioning
confidence: 99%
“…Furthermore, one of the best-performing function prediction methods in the CASP9 experiment [3], a blind assessment of protein structure and function prediction, was COFACTOR [30], a structure-based method. Methods that predict functionally important residues have demonstrated that predictions made using sequence and structure information are more accurate than those made using only sequence information [31,32]. In addition to making accurate predictions, given structures that were determined experimentally, structure-based annotation methods perform with similar accuracy on predicted structures [29,33].…”
Section: Introductionmentioning
confidence: 99%